2016
DOI: 10.1097/gco.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine prevention of chemotherapy-induced ovarian failure

Abstract: More than 10 recent meta-analyses have concluded that GnRHa is beneficial and may decrease the risk of premature ovarian failure and increase the pregnancy rate in survivors. Furthermore, two recent international meetings of experts have concluded that GnRHa is effective and should be offered to every young woman facing gonadotoxic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…Eighteen meta-analyses of RCTs 13 and 4 recent international expert consensus meetings, 28,29,54,58 in addition to many smaller studies, have critically summarized the utility of GnRHa adjuvant co-treatment along with chemotherapy, concluding that this co-treatment significantly reduces the risk of POF and increases the PR in survivors. 1,4-9,13-15,19-63 Three recent, large prospective RCTs in patients with breast cancer support the use of GnRHa cotreatment for fertility preservation. 34,35,46 The US, POEMS–SWOG/S0230 study enrolled only hormone receptors (HR)-negative breast cancer patients, 34 whereas most patients in the Italian PROMISE–GIM6 …”
Section: Past and Present Experience Using Gnrh Analogs For Fertilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Eighteen meta-analyses of RCTs 13 and 4 recent international expert consensus meetings, 28,29,54,58 in addition to many smaller studies, have critically summarized the utility of GnRHa adjuvant co-treatment along with chemotherapy, concluding that this co-treatment significantly reduces the risk of POF and increases the PR in survivors. 1,4-9,13-15,19-63 Three recent, large prospective RCTs in patients with breast cancer support the use of GnRHa cotreatment for fertility preservation. 34,35,46 The US, POEMS–SWOG/S0230 study enrolled only hormone receptors (HR)-negative breast cancer patients, 34 whereas most patients in the Italian PROMISE–GIM6 …”
Section: Past and Present Experience Using Gnrh Analogs For Fertilitymentioning
confidence: 99%
“…1,4-9,13-15,19-37 Therefore, this noninvasive and inexpensive treatment has gained ubiquitous interest and popularity. 1,4-9,13-15,19…”
Section: Past and Present Experience Using Gnrh Analogs For Fertilitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is characterized by primary or secondary amenorrhea accompanied by increased blood gonadotropin levels and reduced levels of estrogen. The clinical features primarily include symptoms related to low estrogen such as depression, facial flushing, and low libido (1,2). Roussev et al examined 1,858 women with natural amenorrhea and demonstrated that the incidence of POF was <1% before the age of 40 years, and <1/1,000 in women aged under 30 years (3).…”
Section: Introductionmentioning
confidence: 99%